Effects of the functionalization on the performance of graphene oxide-based membranes in the desalination and wastewater treatment: A new classification of functionalizing material - Ayala Claveria, Martin (2024)
Graphene oxide membranes have emerged as cutting-edge materials in desalination and wastewater treatment technologies due to valuable attributes such as ready accessibility, mechanical strength, chemical affinity, high water permeability, and pollutant selectivity. However, a significant challenge arises from the distortion of the nanochannels responsible for water transport due to the hydration of oxidized groups over the graphene oxide nanoplates. This compromises selectivity and alters water transport dynamics. To surmount this drawback, innovative strategies involve the incorporation of additives, or crosslinkers, into the graphene oxide matrix to stabilize these critical nanochannels. This comprehensive review investigates the performance of graphene oxide membranes for desalination and wastewater treatment, where graphene oxide was functionalized through crosslinker integration. A novel classification based on the connector element is considered for relating the crosslinker nature and performance in water treatment, accompanied by a statistical analysis highlighting key factors influencing the performance. It was found that additives based on metallic connectors offer a high likelihood of obtaining high performance while incorporating oxygen-based additives shows the highest performance. Furthermore, the hydrophobic character of the selective graphene oxide layer arises as the key factor in determining the final performance in water depuration.